PERTANGGUNGJAWABAN PIDANA DAN PEMBUKTIAN PADA TINDAK PIDANA SANTET MENURUT KUHP NASIONAL (Jurnal Pendidikan dan Bahasa Sastra Harapanan, 2025)
According to National Criminal Code (KUHP) Law Number 1 of 2023, this study addresses criminal culpability and evidence in cases of witchcraft. This study's backdrop is based on the reality that some individuals still believe in occult and mystical sciences and that there are examples of witchcraft that hurt the community, despite the fact that these cases are sometimes hard to establish legallyThis research aims to evaluate the legal factors that govern criminal responsibility and the methods of evidence in witchcraft trials. Using a normative approach, legal analysis of laws and case studies is the study methodology employed. The findings demonstrated that even while witchcraft is not specifically regulated by the National Criminal Code, the offender may nevertheless be prosecuted using criminal law principles. The conclusion of this research emphasises the need for strengthening regulations and better understanding of the law to handle witchcraft cases, as well as the importance of strong evidence to support a fair judicial process.